2019
DOI: 10.2196/12024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mock Facebook Workday Comments on Public Perception of Professional Credibility: A Field Study in Canada

Abstract: Background There is considerable discussion of risks to health professionals’ reputations and employment from personal social media use, though its impacts on professional credibility and the health professional-client relationship are unknown. Objective The aim of this study was to test the extent to which workday comments posted to health professionals’ personal Facebook profiles influence their credibility and affect the professional-client relationship. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…These findings showed that laypeople are enticed by images of the face that represent general orthodontic treatments, not the mechanical aspects of the treatment. Weijs et al [3] analyzed the perception of credibility based on comments by health professionals on Facebook and observed that credibility had a major influence on the participants' desire to become a client of these health professionals. They also concluded that positive comments related to a professional's daily work were reflected as a perception of greater credibility [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings showed that laypeople are enticed by images of the face that represent general orthodontic treatments, not the mechanical aspects of the treatment. Weijs et al [3] analyzed the perception of credibility based on comments by health professionals on Facebook and observed that credibility had a major influence on the participants' desire to become a client of these health professionals. They also concluded that positive comments related to a professional's daily work were reflected as a perception of greater credibility [3].…”
Section: Discussionmentioning
confidence: 99%
“…A self-administered questionnaire developed by the authors according to the study of Weijs et al [ 3 ] using the Qualtrics digital platform (Salt Lake, UT, USA) was used for data collection. Participants could access the questionnaire digitally using a computer, smartphone, or tablet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, fake news may reach citizens in different ways, depending on their age, culture, and other factors [19]. Moreover, research shows that social media and related global digital media content influence discourses about professions and how citizens perceive them, including public health professionals [20]. For instance, many public health programs aimed at children and youth have physical education at the core of their initiatives [21,22].…”
Section: The Context In Which Fake News Is Spreadmentioning
confidence: 99%